The Shear Layer of I-53° Type Cylinder as Passive Control for Main Cylinder Drag Force Modification: A Numerical Analysis - Louis, Hendri; Sakti, Gunawan; Widodo, Wawan Aries; Aisyah, Imaniar Fitri (JMES The International Journal of Mechanical Engineering and Sciences, 2024)
Numerous engineering disciplines have conducted a substantial study on cylinder-flowing airflow. There are several engineering uses for this flow arrangement, and it remains one of the primary research issues in aerodynamics. Due to the separation of the flow passing through the cylinder, the circular cylinder shows a significant dynamic drag. Ansys Fluent® was used in this study to construct the aerodynamic forces of the central cylinder and its disturbance in laminar flow in 2D. This investigation was conducted using the main cylinder with a diameter of 60 mm, an I-53o type disturbance cylinder, a space of s/D=1.375 between the two cylinders' central points, and a Reynolds number Re = 5.3 × 104 at velocity U = 14 m/s. The transition k-kl-ω (3 eqn) turbulence model was used in this simulation. By comparing various measuring parameters between single and tandem cylinders, this study showed that tandem cylinders offer good aerodynamic performance. The investigated measurement parameter is the coefficient of pressure (Cp), representing the degree of separation delay surrounding the central cylinder. The lift coefficient (CL) reduces by 15%, the coefficient of drag (CD) drops by 46.95%, and the appearance of the pressure and wind speed contours depicted the separation delay and decrease in pressure drag.